A pro-oxidant property of vitamin C to overcome the burden of latent Mycobacterium tuberculosis infection: A cross-talk review with Fenton reaction - Gaglani, Pratikkumar; Dwivedi, Manish; Upadhyay, Tarun Kumar; Kaushal, Radhey Shyam; Ahmad, Irfan; Saeed, Mohd (Frontiers in Cellular and Infection Microbiology, 2023)
Mycobacterium tuberculosis is a prominent human pathogen, which has caused several million fatalities per year. In past decades, it has been readily treated with regular first-line and second-line medications; in the present condition, the conventional therapies are no longer effective against the bacterium owing to the drug resistance developed towards the available medications - antibiotics. To address the growing instances, globe wide, researchers have focused towards vitamins having bactericidal characteristics and found them helpful when supplied together with first-line medications. Vitamin C (VC) a regime which can induce Fenton reaction has the ability to sterilize the Mycobacterial culture. Among all microorganisms, Mycobacterium tuberculosis shows particular sensitivity towards VC. VC's bactericidal efficacy counter to Mycobacterium tuberculosis is, elevated ferrous ion concentrations dependent and reactive oxygen species (ROS) generation due to its pro-oxidant properties, and it has a pleiotropic influence on a number of biological processes. This review explains the existing medications, acquired resistance to drugs and impact of VC on M.tb. like the formation of free radicles (Fenton reaction) and bactericidal effects.